Analysis of the communication network among citizens on twitter in violence victims in Indonesia - Tinuk Dwi Cahyani,; Muhamad Helmi Md. Said,; Muhamad Sayuti Hassan, (Penerbit Universiti Kebangsaan Malaysia, 2024)
The high level of violence in Indonesia, especially against women and children, requires special attention from all parties. It needs to be improved not only from the government’s side but also from the community and in any form. This research aims to find out the communication network of civilians on Twitter as one of the social media platforms for dealing with victims of violence in Indonesia. A qualitative analysis method was employed to collect data and information on the communication and interaction of KontraS in its role as a non-governmental organization. This research also utilized Software NVivo 12 Plus to analyse the data to find out the form of the network communication of KontraS in dealing with the violence victims in the state through Twitter. The research results have revealed that KontraS utilizes Twitter for communication and interaction to build organizational networks involving several parties, where information on human rights issues and violence is posted with hashtags to help disseminate information that leads to the formation of the organizational power of KontraS to support the advocacy of policy that is pro-human rights- and violence-related issue handling in Indonesia. The communication and interaction of KontraS on Twitter impact the dynamic of discussion on the issues of human rights and violence in Indonesia. This research, however, only focused on Twitter data. Thus, further research is expected to involve more data on other social media, such as Facebook and YouTube.